Holding water for the city: Emergent geographies of storage and the urbanization of nature. (December 2022) - Randle, Sayd
In the US West, water stories are often aqueduct stories, narratives of moving the vital resource from one place to another. This paper, in contrast, explores nascent efforts to keep the water still, in the name of helping buffer cities from the anticipated impacts of climate change. Scripted as potential holding sites for an urban water reserve, aquifers and the task of filling them now orient a range of policies and material investments across Southern California. Building on writings that explore the multi-scalar politics of storing and stockpiling vaccines, resources, and lively or uncooperative commodities, this analysis approaches storage as a key moment within circulation, a dynamic, constitutive stillness that conditions flows. Three early-stage subterranean water stockpiling projects connected to the City of Los Angeles are explored, and used to demonstrate how the pursuit of storage is remaking material and political relationships within and between urban jurisdictions, while complicating long-fraught urban–rural relations within the region's waterscape. These shifts suggest the value of reorienting the notion of the urbanization of nature to better attend to the geographies of resource storage, in addition to those of resource flows and circulations.